PENGARUH KOMPONEN RISK BASED BANK RATING (RBBR) TERHADAP PROFITABILITAS PERBANKAN - Anggi Tiara Novira; Reni Oktavia; Yuztitya Asmaranti (Faculty of Economics and Business, 2020)
This study aims to analyze the effect of Risk Based Bank Rating (RBBR) component implementation to the financial performance of conventional commercial banks in Indonesia. The RBBR component is presented by using variables: Non Performing Loan, Loan to Deposit Ratio, Good Corporate Governance, Operational Efficiency Ratio, Net Interest Margin, Capital Adequacy Ratio. Meanwhile, financial performance is measured using Return On Assets (ROA). This study used quantitative methods with secondary data obtained from the websites of each conventional commercial bank. The research sample was selected by using purposive sampling in order to obtain 25 conventional commercial banks in Indonesia during 2010-2019. Data analysis used multiple linear regression analysis by IBM SPSS Statistics 26 program. The results of this study indicate that Non Performing Loan (NPL), Good Corporate Governance (GCG), Capital Adequacy Ratio (CAR) have no effect on the financial performance of conventional commercial banks. Meanwhile, the Loan to Deposit Ratio (LDR) and Operational Efficiency Ratio (REO) have a negative effect on the financial performance of conventional commercial banks, and the Net Interest Margin (NIM) has positive effect on the financial performance of conventional commercial banks.